Unlocking superior dispersion uniformity in powder-binder feedstock for near net-shaping via Hansen solubility-guided design - Chen, Mengxiong; Fu, Yang; Xiong, Huiwen; Zhang, Lei; Zou, Jianpeng; Zhou, Kechao (Materials today physics, 2025)
Powder injection molding and extrusion-based 3D printing which using thermoplastic feedstock, are pivotal manufacturing technologies. Feedstock design critically influences product quality, yet a systematic scientific methodology remains lacking. In this study, we proposed a Hansen solubility parameter (HSP)-guided strategy leveraging polymer intermolecular interaction to design and optimize polyformaldehyde (POM)-based binder systems for cermet powder. Different functional polymers/groups were evaluated within the POM binder matrix. We demonstrated that polystyrene (PS) improved the dispersion uniformity of the binder phase and reduced the feedstock viscosity and crystallization tendency. Epoxy resin (EP) adsorbed onto the powder surface through chemical bonding, improving powder and binder dispersibility through its strong interaction with POM compatibility. The HSP-optimized feedstock demonstrated improved phase dispersion, reduced binder aggregation, and enhanced debinding and molding properties compared to conventional POM-based feedstock. This work validated the HSP-guided strategy as a viable design tool for thermoplastic feedstocks, providing a design framework applicable to both powder injection molding and extrusion-based 3D printing. [Display omitted] •An HSP-based strategy leveraging polymer intermolecular interactions was proposed to design and optimize PIM feedstocks.•PS as backbone binder improved binder compatibility, reduced viscosity and crystallization of feedstock.•EP chemically bonded to powder surfaces, enhancing POM-powder dispersibility via its strong interactions with POM.•HSP-optimized feedstock exhibited superior dispersion, debinding and molding properties vs. conventional POM feedstock.